Tahlilan dan Pendidikan Moderasi Beragama: Dampaknya terhadap Toleransi Agama di Perkotaan - Septian Arief Budiman; Fil Isnaeni (Jurnal Keislaman)
This research aims to examine the role of the tahlilan religious tradition as a medium for religious moderation education in the context of urban society.  Tahlilan, which is a religious tradition often practiced among the Muslim community in Indonesia, not only serves as a form of worship but also as a social space that allows interaction among residents with diverse religious and cultural backgrounds.  Through a qualitative approach, this research analyzes how tahlilan serves as a means to introduce and internalize the values of religious moderation, such as tolerance, appreciation of differences, and living harmoniously in a pluralistic society.  The research results show that tahlilan in urban communities not only strengthens interpersonal relationships but also serves as informal education that reinforces values of togetherness and mutual respect in the context of religious and cultural pluralism.  Therefore, the tahlilan tradition can be viewed as one form of effective religious moderation education in addressing social challenges in urban communities.  This research contributes to the understanding of the importance of religious practices in shaping moderate and tolerant attitudes amidst diversity.